A Journey from June 2018 to October 2021 with N,N-Dimethylformamide and N,N-Dimethylacetamide as Reactants - Jacques Muzart (MDPI AG, 2021)
A rich array of reactions occur using N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc) as reactants, these two amides being able to deliver their own H, C, N, and O atoms for the synthesis of a variety of compounds. This account highlights the literature published since June 2018, completing previous reviews by the author.